Freshwater lobster cultivation (cherax quadricarinatus): Post Covid-19 traumatic healing and economic revitalization - Gunawan Refiadi; Dodi Gunawan; Mujiarto Mujiarto; Acep Wagiman; Rislah Anini Tasnim; Alayka Syarifa Putri (Universitas Muhammadiyah Magelang, 2022)
There are at least two impacts of Covid-19, mental trauma due to the loss of a loved family member and the decline of livelihoods. However, post-pandemic, life must go on. Families left behind need trauma healing, while those who have run aground must generate new economic opportunities. A service idea was rolled out in the form of training on freshwater crayfish cultivation which has potential and has prospective economic value. The activity is intended for sixbee community partners in the form of training on the introduction and practice of freshwater crayfish cultivation using the aquarium method. The results show that this activity has succeeded in providing benefits to partners through facilitation of trauma healing and socialization of red claw freshwater crayfish cultivation as a new economic opportunity after Covid-19.